Insomnia and excessive daytime sleepiness in women and men receiving methadone and buprenorphine maintenance treatment. (24th August 2019) - Hallinan, Richard; Elsayed, Mahmoud; Espinoza, David; Veillard, Anna-Sophie; Morley, Kirsten C.; Lintzeris, Nick; Haber, Paul
Abstract: Background: Insomnia and excessive daytime sleepiness (EDS) are reported to be common in methadone maintenance treatment (MMT) but much less is known about these symptoms in buprenorphine maintenance treatment (BMT) and in women compared with men. Methods: Cross sectional study of recipients of BMT ( n  = 113, 47 women), MMT ( n  = 184, 94 women), people using opioids nonmedically (nonopioid agonist treatment, non-OAT: n  = 87, 31 women) and a reference group with no opioid use (RG; n  = 105, 53 women) in Australia. Measures included Athens Insomnia Scale, Epworth Sleepiness Scale, the Hospital Anxiety and Depression Scale, and other substance use. Results: Insomnia (Athens Insomnia Scale, total ≥10) was highly prevalent among all people who use opioids (BMT 46.0–68.1%; MMT 55.4–69.6%; non-OAT 58.6–80.5%), did not differ significantly among these groups, and was significantly associated with anxiety and depression. EDS (Epworth score >10) was found in 14.2% of BMT, 22.8% of MMT, 35.6% of non-OAT groups, and 11.4% of the RG, and was significantly associated with depression overall. Fewer people had Epworth score >15 indicating more severe EDS (BMT 4.4%, MMT 6.0%; non-OAT 13.8%; RG 1.9%). Insomnia and EDS did not differ by sex or by opioid dose, nor were they significantly associated with other drug use, housing stress or social security status. Conclusions: Insomnia was common in people receiving OAT and using opioids non-medically, and associated with anxiety and depression. Clinicians should consider the possibility of daytime sleepiness in people receiving BMT and MMT, and in people using opioids nonmedically.